Manifestations of Differential Cultural Capital in a University Classroom: Views from Classroom Observations and Focus Group Discussions in a South African University - Edmore Mutekwe (Journal of Education and Learning (EduLearn), 2014)
Based predominantly on Pierre Bourdieu’s social and cultural reproduction theory, particularly his notions of cultural capital and symbolic violence, this paper explores how first year post graduate Diploma in Higher Education (PGDHE) university students from diverse socio-linguistic backgrounds differ in the levels at which they understand and express themselves in classroom activities. The paper’s thesis is that the diverse nature of South African classrooms presents a number of challenges not only for students but also for educators in terms of the use of English as a medium of instruction or the language for learning and teaching (LOLT). Owing to the fact that the South African Language in Education Policy (LiEP) of 1997 empowers both learners and educators in schools to use any of the eleven South African official languages as a LOLT wherever that is reasonably possible, students whose English backgrounds were deficient in enculturating them in the use of English as a learning tool often encounter challenges in expressing their ideas in the classroom, whether in writing or in oral presentations. The discussion is anchored in the data elicited through two data collection methods, lesson observations in a Diploma in Higher Education, Research class composed of students from diverse racial and ethnic backgrounds and through focus group discussion sessions with 40 multi-ethnic Diploma in Higher Education students from the same classroom. The data management and analysis for this study was done thematically, with views emerging from the observations and focus group discussions being clustered into superordinate themes for convenience of the discussion of the findings. The findings of this study were that students from affluent socio-economic backgrounds who enter university with a rich and relevant English linguistic capital, values and attitudes enjoy an enormous advantage compared to their counterparts whose social class and linguistic backgrounds lack the cultural capital cherished in university as conducive for educational success. The study thus recommends that the South African LiEP policy needs to be repealed so that it spells out unequivocally the LOLT especially in institutions of higher learning.